Determination of phenolic compounds in extracts of Amazonian medicinal plants by liquid chromatography-electrospray tandem mass spectrometry. Issue 7 (8th February 2017) - Faccin, Henrique; Loose, Roberta Fabricio; Viana, Carine; Lameira, Osmar A.; de Carvalho, Leandro Machado
Abstract : A method for the separation, identification and quantification of 24 phenolic compounds using ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) was developed and validated. Abstract : A method for the separation, identification and quantification of 24 phenolic compounds using ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS) was developed and validated. Six species of traditional medicinal plants from the Brazilian Amazon region were studied ( Mansoa alliacea, Bauhinia variegata var. variegata, Bauhinia variegata var. alboflava, Connarus perrottetii var. angustifolius, Cecropia obtusa and Cecropia palmata ). The analytes were separated by a reversed-phase SB-C18 column (2.1 × 50 mm, 1.8 μm) using a gradient elution of 7 min composed of 0.1% acetic acid in water (v/v) and acetonitrile, at a constant flow rate of 0.8 mL min −1 . The limit of detection for the analytes ranged between 0.5 and 130.3 μg L −1 . Intra- and inter-day precision showed satisfactory results and the recoveries obtained for the 24 analytes varied between 91.7 and 111.9% for most of the evaluated matrices. Quantifications were performed with the standard addition method ( r > 0.99) using the data acquired in a multiple reaction monitoring (MRM) mode. Rutin, apigenin, vanillic acid, caffeic acid, ferulic acid, p -coumaric acid and trans -cinnamic acid were found in all the studied plants. However, we highlight the high contents of rutin in varieties of Bauhinia variegata (up to 2.52 mg g −1 of plant), chlorogenic acid in species of genus Cecropia (up to 0.57 mg g −1 of plant) and catechin in Connarus perrottetii var. angustifolius (1.77 mg g −1 of plant).